Reading printed versus online texts. A study of EFL learners strategic reading behavior - Usó, Esther; Ruiz-Madrid, Mª Noelia (International Journal of English Studies, 2009)
With the development of the WWW and Internet, hyperreading has become an issue for discussion in the educational field and more specifically in the field of English as a second or foreign language. Yet, very little is known about its nature concerning the reading process. Therefore, the purpose of this paper is twofold: first, to examine whether the hypertextual medium affects learners’ reading comprehension and, second, to analyze learners’ use of strategies in hard copy and online reading contexts. Fifty university students from the discipline of Tourism read a research article in English taken from an online journal. Half the students (n = 25) read it in a printed format and the other half (n = 25) read it in its online version. Materials included an English academic reading test to measure learners’ comprehension of the academic passage and a reading strategy questionnaire to determine which strategies were employed by students. Statistical analyses revealed that the hypertextual medium 1) did not affect learners’ overall reading comprehension, and 2) promoted the use of reading strategies, including both top-down and bottom-up strategies. These results are discussed and suggestions for further research are given.